Step
*
of Lemma
gamma-neighbourhood-prop2
∀beta:ℕ ⟶ ℕ. ∀n0:finite-nat-seq(). ∀x:ℕ.
  ((¬((beta x) = 0 ∈ ℤ))
  
⇒ (∃x1:ℕx + 1
       ((¬((beta x1) = 0 ∈ ℤ))
       ∧ (∀y:ℕx1. ((beta y) = 0 ∈ ℤ))
       ∧ ((gamma-neighbourhood(beta;n0) n0**λx.x1^(1)) = (inl 1) ∈ (ℕ?))
       ∧ ((gamma-neighbourhood(beta;n0) n0**λx.(x1 + 1)^(1)) = (inl 0) ∈ (ℕ?)))))
BY
{ (UnivCD THENA Auto) }
1
1. beta : ℕ ⟶ ℕ
2. n0 : finite-nat-seq()
3. x : ℕ
4. ¬((beta x) = 0 ∈ ℤ)
⊢ ∃x1:ℕx + 1
   ((¬((beta x1) = 0 ∈ ℤ))
   ∧ (∀y:ℕx1. ((beta y) = 0 ∈ ℤ))
   ∧ ((gamma-neighbourhood(beta;n0) n0**λx.x1^(1)) = (inl 1) ∈ (ℕ?))
   ∧ ((gamma-neighbourhood(beta;n0) n0**λx.(x1 + 1)^(1)) = (inl 0) ∈ (ℕ?)))
Latex:
Latex:
\mforall{}beta:\mBbbN{}  {}\mrightarrow{}  \mBbbN{}.  \mforall{}n0:finite-nat-seq().  \mforall{}x:\mBbbN{}.
    ((\mneg{}((beta  x)  =  0))
    {}\mRightarrow{}  (\mexists{}x1:\mBbbN{}x  +  1
              ((\mneg{}((beta  x1)  =  0))
              \mwedge{}  (\mforall{}y:\mBbbN{}x1.  ((beta  y)  =  0))
              \mwedge{}  ((gamma-neighbourhood(beta;n0)  n0**\mlambda{}x.x1\^{}(1))  =  (inl  1))
              \mwedge{}  ((gamma-neighbourhood(beta;n0)  n0**\mlambda{}x.(x1  +  1)\^{}(1))  =  (inl  0)))))
By
Latex:
(UnivCD  THENA  Auto)
Home
Index